A flexible tooling and local consolidation process to manufacture 1D lattice truss composite structure. (5th June 2015) - Lai, Changliang; Wang, Junbiao; Liu, Chuang; Fan, Hualin; Xu, Binbin; Wu, Kaijing
Abstract: A flexible tooling for one-dimensional (1D) lattice truss composite structure (LTCS) was presented. To facilitate the tooling design, the design of its key parts was mathematically modeled. Additionally, to reduce the consolidation workloads, a local consolidation method was employed. In the locally-consolidated specimen, aramid threads are only wrapped around longitudinal members, which can reduce at least two-thirds time required by the entire consolidation process. Using the flexible tooling and adopting entire consolidation, local consolidation and non-consolidation processes, 1D LTCS specimens were manufactured. Compression tests were carried out to evaluate their mechanical performances. The test results indicate that the local consolidation method captures 48% improvement in compression strength compared to the non-consolidated specimen, and does not weaken the compressive stiffness and strength compared to the entire consolidation process.